ECMO combined with sequential oxygen therapy in drowning-induced ARDS: a case report - Wu, Yaxu; Zhai, Rui; Wang, Boyuan; Zhao, Pengpeng; Zhao, Lijun; Cui, Huanhuan; Chen, Chen; Hu, Mei (Frontiers in Medicine, 2025)
A 35-year-old male was admitted with drowning-induced cardiorespiratory arrest. Initial assessment revealed acute respiratory distress syndrome (ARDS), pneumothorax and refractory hypoxemia. Despite mechanical ventilation and thoracostomy tube placement, his condition deteriorate. Prompting urgent initiating of veno-veous extracorporeal membrane oxygenation (V-V ECMO). Respiratory support was dynamically adjusted through sequential oxygen therapy, balancing oxygenation optimization with mitigation of ventilator-induced lung injury. Concurrent targeted antimicrobial therapy and intensive care management led to gradual clinical improvement, culminating in successful ECMO weaning and eventual recovery. This case highlights the potential of integrating ECMO with sequential oxygen therapy to address complex pathophysiological challenges in drowning-associated ARDS.